Optimization of NTRU Prime asymmetric encryption algorithm - Kachko, O.G.; Gorbenko, Yu.I.; Esina, M.V.; Akolzina, O.S. (Radiotekhnika, 2017)
The results of algorithms optimization for the post-quantum mechanism of asymmetric encryption NTRU Prime are given. Namely: module reduction, blinding polynomial calculation, encryption and decryption algorithms. A comparative analysis of different polynomials multiplications is also given.